Synthesis of DNA fragments containing 5,6-dihydrothymine, a major product of thymine gamma radiolysis. - Schulhof, J C (1988)
5,6-Dihydrothymine is one of the most important products of base damage by gamma irradiation of DNA in anoxic conditions. This modified base is unstable in the deprotection conditions used for classical synthesis of oligonucleotides. For its incorporation in synthetic DNA fragments, a new set of amino protecting groups has been developed. The 5,6-dihydrothymidine phosphoramidite was successfully employed for the synthesis of two 14-mers and one 17-mer bearing this defect at positions corresponding to restriction enzymes sites. The presence of the modified base still intact in the oligonucleotides was evidenced by mass spectrometry in pyrolytic conditions.